The model of working process of the boom lifting and lowering mechanism with an additional damper in the form of hydrodiode - S. Yu. Kaigorodov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
In hydraulic and pneumatic systems, due to the many factors of their operation, pressure and flow fluctuations inevitably occur. Such fluctuations are formed during the operation of gas-liquid aggregates, during the passage of resistance flow, and their appearance is influenced by the material of manufacture (its rigidity) of the system. As a rule, such phenomena in systems are undesirable and lead to changes in the performance characteristics of the system relative to the calculated data. Thus, there are various mechanisms to "smooth out" the fluctuations of the systems. In hydraulic systems, in particular in lifting machines, I often use special devices for this — dampers. In this paper, it is proposed to use a hydrodiode as a damper. Having a different flow rate in the forward and reverse direction, it provides a different flow-drop characteristic when lifting and lowering the boom. This effect allows you to improve the positioning of the crane boom when lifting and lowering the boom.